2003
DOI: 10.1021/np020372g
|View full text |Cite
|
Sign up to set email alerts
|

Polyprenylated Benzophenones from Garcinia assigu and Their Potential Cancer Chemopreventive Activities

Abstract: In a further study on the chemical constituents of Garcinia assigu, two new benzophenones corresponding to the 13-O-methyl ethers (1 and 2) of the known isogarcinol and garcinol, respectively, were isolated and characterized, along with known benzophenones (3-6). Inhibitory effects of the benzophenones isolated from this plant on Epstein-Barr virus early antigen (EBV-EA) activation induced by 12-O-tetradecanoylphorbol-13-acetate (TPA) in Raji cells and their radical-scavenging ability against 1,1-diphenyl-2-pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
54
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(58 citation statements)
references
References 14 publications
3
54
0
1
Order By: Relevance
“…[1][2][3][4][5][6] Knowledge of the chemical characteristics of biflavonoids from the genus has accumulated since the 1970s, and research into many species has shown that the majority of these biflavonoids are simply 3′-8″ and 3-8″ linked types, which are represented by amentoflavone and morelloflavone.…”
Section: Isolation Of Six Isoprenylated Biflavonoids From the Leaves mentioning
confidence: 99%
“…[1][2][3][4][5][6] Knowledge of the chemical characteristics of biflavonoids from the genus has accumulated since the 1970s, and research into many species has shown that the majority of these biflavonoids are simply 3′-8″ and 3-8″ linked types, which are represented by amentoflavone and morelloflavone.…”
Section: Isolation Of Six Isoprenylated Biflavonoids From the Leaves mentioning
confidence: 99%
“…Secondary cyclizations involve the ␤-diketone and pendant olefinic groups affording adamantanes, homoadamantanes and dihydrofuran-or pyran-fused structures [1]. PPBs exhibit a wide variety of biological activities, the most interesting of which are cytoprotection against HIV-1 [2,3], antibacterial activity against methicillin-resistant Staphylococcus aureus [4 -6], antioxidant [7][8][9], and cytotoxic activity [9 -14].…”
mentioning
confidence: 99%
“…Garcinol is reported to have dose dependent activity against prostate cancer cell lines PC-3, LNCaP and DU-145 [26]. The types of cancer on which cytotoxic effect of garcinol is tested are breast cancer [27], Burkitt lymphoma [28], Colon cancer [29], esophageal cancer [27], hepatocellular carcinoma [30]. We assume that garcinol exhibits anticancer activity against neuroblastoma through triggering the apoptotic cascade.…”
Section: Choudhury Et Almentioning
confidence: 99%